Biting midges of the subfamily Forcipomyiinae (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species - Alwin-Kownacka, Alicja; Szadziewski, Ryszard; Szwedo, Jacek (Zootaxa, 2016)
Middle East biting midges of the genera Atrichopogon Kieffer and Forcipomyia Meigen, subfamily Forcipomyiinae Lenz, covering 41 species are reviewed. Two new species are described and illustrated: Forcipomyia (F.) siverekensis Alwin & Szadziewski sp. nov. and Forcipomyia (Microhelea) borkenti Alwin & Szadziewski sp. nov. The list includes 16 species of Atrichopogon and 25 of Forcipomyia. Nine species previously described by Vimmer and Kieffer from the Middle East are treated as nomina dubia and not included in the list.        Keys to identification of Atrichopogon and Forcipomyia species of the Middle East are also provided.